Factors determining the outcomes of immune imprinting after repeated orthoflavivirus infections - Salem, Gielenny M.; Chen, Fan-Chi; Cai, James J.; Chao, Day-Yu (Frontiers in Immunology, 2025)
Orthoflaviviruses, a group of arthropod-borne viruses, represent a significant global health threat, with hundreds of millions of infections each year, often leading to severe clinical outcomes. This Review elucidates the complexities of immune imprinting, also known as original antigenic sin (OAS), and its influence on immune responses to repeated, heterologous orthoflavivirus infections. We examine how initial exposure to a virus can shape subsequent immune responses, potentially resulting in sub-optimal binding of pre-existing antibodies to related but distinct viruses. Although OAS is often linked with adverse outcomes, such as enhanced disease severity in dengue due to antibody-dependent enhancement, we re-introduce the concept of “antigenic seniority,” which highlights the potential advantages of prior exposures by promoting cross-protection against related variants. This perspective underscores the dual nature of immune imprinting and its implications for vaccine development and therapeutic strategies against orthoflavivirus infections. By exploring the delicate balance between protective and maladaptive immune responses, we emphasize critical considerations for developing effective vaccines and interventions in the context of evolving viral threats.